the Diversity of Lepidopteron pests and assessing their infestation ratios and damages on cruciferous crops - Sara Tareq Abdulrahman; Nawzad Bawakir Kadir (Zanco Journal of Pure and Applied Sciences, 2023)
A field research was conducted in the Grda Resha Research Station-College of Agricultural Engineering Sciences-Erbil-Kurdistan region-Iraq, to investigate the pestiferous lepidopteron insects associated with cruciferous crops and assessing the rate of their infestation at two different periods of crop age as well as estimating the damages caused by pestiferous insect complex in the field of crucifers including cabbage( varieties Zalal and Hanar), broccoli (varieties Ajas and Wisdom), and cauliflower ( varieties Kasper and Organza), the experiment was carried out using RCBD design. The result showed that there are six pestiferous insects belonging to four different families within Order Lepidopter including Pieris rapae (L.), Trichoplusia ni (Hübner), Pontia daplidice (L.), Hellula undalis (Fabricius), Plutella xylostella (L.), Pieris brassicae (L.). the study displayed that the cabbage crop variety Zalal was the most preferable host plant and occupied the highest percentage of infestation by all pestiferous lepidopteron insects under the current study at both leaf and maturity stage and the same variety (Zalal) also for damage occupation due to larvae of studied pestiferous lepidopteron insects which was occupied the highest damage percentage.